Profitability, Leverage, and Firm Size: Their Impact on Stock Price of Property and Real Estate Companies Listed on IDX - Harits, Abdul Gamal; Djazuli, Atim (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to examine and analyze the influence of profitability, leverage, and firm size on stock price. Out of 94 property and real estate companies listed on the Indonesia Stock Exchange from 2020 to 2023, 21 were selected as samples using purposive sampling, resulting in 84 observations. In this study, profitability is measured by Return on Assets, leverage by Debt-to-Equity Ratio, and firm size by total assets. The quantitative data, in the form of numerical figures, were obtained from secondary sources through the official website of the Indonesia Stock Exchange. The results of the multiple linear regression analysis show that (1) profitability has an insignificant effect on stock price, (2) leverage has a significant effect on stock price, and (3) firm size has a significant effect on stock price.